The Influence of Professional Commitment, Locus of Control and Machiavellian on Whistleblowing Intention with Organizational Commitment as a Moderating Variable - Fajrin, Vira; Tubagus Ismail; Wulan Retnowati (Indonesian Journal of Economic & Management Sciences, 2024)
The aim of this research is to determine the influence of professional commitment, locus of control and Machiavellianism on whistleblowing intention with organizational commitment as a moderating variable. The research uses quantitative methods, as well as descriptive design and causal design. The research population was employees in the Regional Apparatus Organization (OP) of Banten Province who served as section heads, section heads and financial administration officials. Sample of 64 respondents using purposive sampling technique. Data analysis uses path analysis. The results show variations in the substantive influence of the variables professional commitment, locus of control and Machiavellian with organizational commitment as a moderator of 82.9%. Furthermore, professional commitment has a positive effect on whistleblowing intention, locus of control has a positive effect on whistleblowing intention, Machiavellian has no effect on whistleblowing intention, organizational commitment moderates the effect of professional commitment on whistleblowing intention, organizational commitment does not moderate the effect of locus of control on whistleblowing intention, and commitment The organization does not moderate the Machiavellian influence on whistleblowing intention